2008
DOI: 10.32725/jab.2008.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pterostilbene on lipids and lipid profiles in streptozotocin-nicotinamide induced type 2 diabetes mellitus

Abstract: Hyperlipidaemia is one of the major risk factors of cardiovascular complication in diabetes. A study was undertaken to evaluate the antihyperlipidaemic activity of pterostilbene. Oral administration of pterostilbene (40mg/kg bodyweight) to streptozotocin-nicotinamide induced diabetic rats for 6 weeks significantly reduced the elevated serum very low density lipoprotein (VLDL) and low density lipoprotein (LDL)-cholesterol levels and significantly increased the serum high-density lipoprotein (HDL)-cholesterol le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 23 publications
3
36
0
2
Order By: Relevance
“…Oral administration of diosgenin significantly lowered PLs in tissues of rats with HFD‐STZ‐induced diabetic rats. Several studies have reported that the increased PL levels in tissues of experimental diabetic rats . An enhanced peroxide radical in diabetes causes membrane damage, which may be responsible for the increased phospholipids .…”
Section: Discussionmentioning
confidence: 95%
“…Oral administration of diosgenin significantly lowered PLs in tissues of rats with HFD‐STZ‐induced diabetic rats. Several studies have reported that the increased PL levels in tissues of experimental diabetic rats . An enhanced peroxide radical in diabetes causes membrane damage, which may be responsible for the increased phospholipids .…”
Section: Discussionmentioning
confidence: 95%
“…We previously demonstrated pterostilbene as a PPARα agonist, and decreased plasma glucose, very‐low‐density lipoprotein (VLDL)‐, low‐density lipoprotein (LDL)‐, and total cholesterol, and increases HDL‐cholesterol levels in hamsters fed a high‐fat diet, effects that are consistent with PPARα activation . Other groups have also reported anti‐diabetic and hypolipidemic properties of pterostilbene . Resveratrol has been reported to bind to PPARα .…”
Section: Introductionmentioning
confidence: 90%
“…The mean values were calculated. Rats were rendered diabetic if FBS level was greater than 250 mg/dl [10].…”
Section: Biochemical Studiesmentioning
confidence: 99%